Solid particle erosion of ceramics - Wellman, R G (Centre for Materials Engineering, 2016)
The zeolite ZSM-5 is well-known for its unique intersecting channel system. This channel system has a great bearing on the shape-selective properties and the long life-times of ZSM-5. In this study, ZSM-5 was modified in various ways to eliminate the external acidity of the catalyst to further improve these properties, and the success and effects of these modifications were investigated primarily using temperature programmed desorption techniques. The internal surface of ZSM-5, a medium pore zeolite, plays a major role in the shape selective properties of this catalyst, due to the diffusional restrictions imposed by the channel system on bulky molecules. Even though the number of acid sites on the external surface is small compared to the total number of acid sites, these easily accessible and non-shape selective acid sites may provide a high turnover rate for non-shape selective reactions. Furthermore, the main cause of deactivation of ZSM-5 is thought to be the formation of polyaromatic molecules on the external surface, which block access to the channels of the catalyst.